2015
DOI: 10.1371/journal.pone.0131626
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phenolic Compound, Chloroxynil, Improves Agrobacterium-Mediated Transient Transformation in Lotus japonicus

Abstract: Agrobacterium-mediated transformation is a commonly used method for plant genetic engineering. However, the limitations of Agrobacterium host-plant interactions and the complexity of plant tissue culture often make the production of transgenic plants difficult. Transformation efficiency in many legume species, including soybean and the common bean, has been reported to be quite low. To improve the transformation procedure in legumes, we screened for chemicals that increase the transformation efficiency of Lotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Andrieu et al [2] found that the transient expression effect of EHA105 strain was better than AGL1 and LBA4404 in rice leaves, while Mishra et al [28] optimized the transient expression system of Withania somnifera and found that LBA4404 strain had the highest infection efficiency. Up to now, there were many strains reported to be able to infiltrate legumes with high expression efficiency, including GV3101 [14], GV2260 [29], EHA105 [14, 30], LBA4404 [31, 32], AGL1 [3, 33] and J2 [8]. In this study, we compared the genetic background of 5 Agrobacterium strains for transient expression in C. intermedia , and the GUS staining results revealed that the EHA101 and LBA4404 had no effect on the leaves of C. intermedia , and GV3101 strain was more suitable for transient expression system compared to EHA105 and AGL1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrieu et al [2] found that the transient expression effect of EHA105 strain was better than AGL1 and LBA4404 in rice leaves, while Mishra et al [28] optimized the transient expression system of Withania somnifera and found that LBA4404 strain had the highest infection efficiency. Up to now, there were many strains reported to be able to infiltrate legumes with high expression efficiency, including GV3101 [14], GV2260 [29], EHA105 [14, 30], LBA4404 [31, 32], AGL1 [3, 33] and J2 [8]. In this study, we compared the genetic background of 5 Agrobacterium strains for transient expression in C. intermedia , and the GUS staining results revealed that the EHA101 and LBA4404 had no effect on the leaves of C. intermedia , and GV3101 strain was more suitable for transient expression system compared to EHA105 and AGL1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nanjareddy et al [12] also used the same method to optimize the transient expression system of Phaseolus vulgaris , and 60%~ 85% of cells on the leaf surface showed GUS staining after infiltrating with suspension containing acetosyringone (a phenolic compound that can attract Agrobacterial cells to the wounded plant tissues via chemotaxis and induces the Vir genes to initiate T-DNA transfer [13]) and Silwet L-77, while the procedure is sophisticated and time-consuming. In order to improve the transient transformation efficiency of Lotus japonicus , Kimura et al [14] has screened out a phenolic compound, Chloroxynil, among a variety of compounds, which is able to increase the efficiency of transient transformation 6 times higher than that of acetosyringone. However, Chloroxynil is expensive and highly toxic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the significantly higher transformation efficiency obtained with acetosyringone highlighted the importance of using phenolics in transforming Chondrus (Figure 4). A significantly higher transformation efficiency was reported in the presence of a phenolic compound (Kimura et al 2015). However, the effects of phenolic compounds such as acetosyringone on transformation efficiency depend on the host types and bacterial strains (Ainsley et al 2001, Wang et al 2002.…”
Section: B C D E Amentioning
confidence: 99%
“…dde2/ein2/pad4/sid2 (Tsuda et al, 2009) and NahG (Rosas-Díaz et al, 2017)]. As an alternative strategy, transformation efficiency can also be enhanced by modifying the virulence of Agrobacterium , which influences plant immunity (Hiei et al, 1994; Ishida et al, 1996; Piers et al, 1996; Rashid et al, 1996; de Groot et al, 1998; Wenck et al, 1999; Rohini and Rao, 2000; Kunik et al, 2001; Komari et al, 2006; Kimura et al, 2015). Accordingly, controlling the immunity responses of target plants is considered a key strategy that could be used to address current inefficiencies in plant transformation.…”
Section: Introductionmentioning
confidence: 99%